EFFECT OF VINE LOAD AND SEAWEED EXTRACT ON THE GROWTH AND YIELD OF GRAPE VINES (VITIS VINIFERA L.), SHATTER AL-ANZ CULTIVAR - M. F. Al-Doori; S. A. Hussein (مجلة الأنبار للعلوم الزراعية)
The experiment was conducted in the grape orchard of the Department of Horticulture and Landscape at the College of Agriculture/Tikrit University during the 2023 growing season, to study the effect of vine load at three levels (30,40 and 50) eyes vine-1 and spraying with seaweed extract at three levels (0,20 and 40) mL L-1 at a rate of three sprays during the study period, with an interval of 10 says between one spray and next, on some characteristics of vegetative growth and yield of grape vines cultivar Shatter Al-Anz,5 years old.Results obtained were summarized as follows: Level 50 eyes vine-1 led to a significant improvement in the studied traits (Leaves area, percentage of chlorophyll, number of clusters, total yield, Percentage of TSS and sugars and total acidity), reaching (9.29 m2, 35.32 SPAD unit, 26.61 cluster vine-1, 9.21 kg, 16.86%, 15.94% and 0.51%) respectively. While level 30 eyes vine-1 led to a significant improvement in the weight of cluster, reaching 412.67 g. Spraying with seaweed extract at two concentrations of 20 and 40 mL L-1 led to a significant increase in the leaves area, percentage of chlorophyll, number and weight of bunches, total yield, percentage of TSS and total sugar comparing to the control treatment, reaching (8.31, 8.56 m2, 34.65, 35.11 SPAD unit, 21.17, 21.50 cluster vine-1, 380, 392 gm, 7.83, 8.29 kg, 16.48, 16.94% and 15.70, 15.93%) respectively. The bilateral interaction between the levels of factors included in the study had a significant effect on most of the studied characteristic